2022
DOI: 10.3390/cells11121954
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Interactions between Oligodendrocyte Precursor Cells and the Neurovascular Unit in Health and Disease

Abstract: Oligodendrocyte precursor cells (OPCs) are mostly known for their capability to differentiate into oligodendrocytes and myelinate axons. However, they have been observed to frequently interact with cells of the neurovascular unit during development, homeostasis, and under pathological conditions. The functional consequences of these interactions are largely unclear, but are increasingly studied. Although OPCs appear to be a rather homogenous cell population in the central nervous system (CNS), they present wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 125 publications
0
4
0
Order By: Relevance
“…To do this, we generated NG2DsRed × CX 3 CR1 +/GFP mice to enable robust visualization of microglia (CX 3 CR1 +/GFP ) and pericytes (NG2DsRed) in fixed brain tissue (Figure 1a,b ). We note that the NG2DsRed line has previously been used to visualize oligodendrocyte progenitor cells (OPCs (Hartmann et al, 2015 ; Nemes‐Baran et al, 2020 ), Supplementary Figure 2 ), and that some OPCs have been found to reside on the vasculature (Pfeiffer, 2022 ; Pfeiffer et al, 2021 ). It is therefore possible OPCs could be mistaken for pericytes when using this genetic line.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…To do this, we generated NG2DsRed × CX 3 CR1 +/GFP mice to enable robust visualization of microglia (CX 3 CR1 +/GFP ) and pericytes (NG2DsRed) in fixed brain tissue (Figure 1a,b ). We note that the NG2DsRed line has previously been used to visualize oligodendrocyte progenitor cells (OPCs (Hartmann et al, 2015 ; Nemes‐Baran et al, 2020 ), Supplementary Figure 2 ), and that some OPCs have been found to reside on the vasculature (Pfeiffer, 2022 ; Pfeiffer et al, 2021 ). It is therefore possible OPCs could be mistaken for pericytes when using this genetic line.…”
Section: Resultsmentioning
confidence: 93%
“…Data were processed in Microsoft Excel and all statistical analysis was performed using GraphPad Prism 9.3.1 (GraphPad, USA). Prior to statistical analysis, data underwent outlier testing using a ROUT test Figure 2), and that some OPCs have been found to reside on the vasculature (Pfeiffer, 2022;Pfeiffer et al, 2021). It is therefore possible…”
Section: Discussionmentioning
confidence: 99%
“…We also note recent reports by Yang et al 58 on AD-relevant activity of CR1 within perivascular macrophages (PVM). Given complex reciprocal interactions between oligodendrocytes and the neurovascular unit 59,60 , simultaneous evaluation of CR1 and AD GWAS loci in PVM and oligodendrocytes may illuminate a shared mechanism that could explain the observed CNS as well as hematological effects in a parsimonious manner. Further investigation of whether rs679515 is associated with alterations of peripheral CR1 may also represent a fruitful path for future study.…”
Section: Discussionmentioning
confidence: 99%
“…Oligodendrocyte precursor cells (OPCs) have crucial functions in BBB maintenance and vessel formation throughout life. In return, they receive trophic support [ 52 ]. By producing and maintaining the myelin sheath as an insulator around axons, they contribute to the critical transmission of nerve impulses.…”
Section: The Neurovascular Unit In Healthmentioning
confidence: 99%